Bilateral Intracranial Vertebral Artery Stenosis Presenting as Recurrent Prolonged Presyncopal Episodes - Banu Sundar; Majaz Moonis; Ajay Wakhloo; Ajit Puri (Case Reports in Neurological Medicine)
Amongst various mechanisms of presyncopal events, posterior circulation disease needs to be considered. This particular mechanism has been underrecognized. We describe a case of a 76-year-old patient with recurrent posterior circulation TIAs, presenting as recurrent prolonged presyncopal events.